Climate change in the dance studio: Findings from the UK Centres for Advanced Training - Nordin-Bates, S.; Quested, Eleanor; Walker, I.; Redding, E. (2012)
Little is known regarding the stability of motivational climate perceptions, or how changes in climate perceptions affect performers. As a result, dancers' perceptions of the prevailing climate within both regional centers for talented young people and local dance schools were assessed longitudinally and in relation to dance class anxiety and self-esteem. Dancers (M age = 14.41, SD = 2.10; 75.7% female) completed standardized questionnaires approximately 6 months apart (Time 1 n = 327; Time 2 n = 264). Both climates were perceived as more task- than ego-involving, but talent center climates were perceived as more task-involving and less ego-involving than local climates. However, dancers found that talent centers became more ego-involving from the middle to the end of the school year, and this change predicted increases in anxiety. Changes in climate perceptions did not predict changes in self-esteem. Results point to the benefits of climates low in ego-involving features if dancers are to experience less anxiety around performance time.